2010
DOI: 10.1073/pnas.0908050107
|View full text |Cite
|
Sign up to set email alerts
|

Direct assignment of EPR spectra to structurally defined iron-sulfur clusters in complex I by double electron–electron resonance

Abstract: In oxidative phosphorylation, complex I (NADH:quinone oxidoreductase) couples electron transfer to proton translocation across an energy-transducing membrane. Complex I contains a flavin mononucleotide to oxidize NADH, and an unusually long series of iron-sulfur (FeS) clusters, in several subunits, to transfer the electrons to quinone. Understanding coupled electron transfer in complex I requires a detailed knowledge of the properties of individual clusters and of the cluster ensemble, and so it requires the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 31 publications
2
98
1
Order By: Relevance
“…The second possibility would be in agreement with the cluster assignment proposed in the preceding paper. In that case, the basis for the interpretation of the DEER data (Roessler et al 2010) would collapse. Also relevant to this point is that spin-spin interaction of a [4Fe-4S] cluster with a flavin radical has not yet been confirmed for Hirst's NADH dehydrogenase which lacks FMN-a.…”
Section: Assignment Of the Epr Signals To Fe-s Clusters In Specific Smentioning
confidence: 99%
See 1 more Smart Citation
“…The second possibility would be in agreement with the cluster assignment proposed in the preceding paper. In that case, the basis for the interpretation of the DEER data (Roessler et al 2010) would collapse. Also relevant to this point is that spin-spin interaction of a [4Fe-4S] cluster with a flavin radical has not yet been confirmed for Hirst's NADH dehydrogenase which lacks FMN-a.…”
Section: Assignment Of the Epr Signals To Fe-s Clusters In Specific Smentioning
confidence: 99%
“…Significance of double electron-electron resonance (DEER) spectroscopy of Hirst's NADH dehydrogenase Roessler et al (Roessler et al 2010) have attempted to assign cluster-cluster interactions observed by double electron-electron resonance (DEER) spectroscopy of the reduced enzyme prepared in their laboratory (Sharpley et al 2006). As a basic reference frame the T. thermophilus structure was used.…”
Section: Assignment Of the Epr Signals To Fe-s Clusters In Specific Smentioning
confidence: 99%
“…viridis [92]. (c) Free energy landscape for the FeS cluster ET chain in bovine mitochondrial complex I [93,94], including estimates for the three low-potential clusters (below 20.4 V) [88]. (d ) Visualization of the free energy landscape within the molecular structure of MtrF: haems are coloured according to their redox potential, with lighter colours corresponding to lower redox potentials and thus a higher position in the free energy landscape.…”
Section: Redox Potentialsmentioning
confidence: 99%
“…Electron (or hole) hopping in proteins can involve a series of redox cofactors as in Complex I (NADH dehydrogenase) of the mitochondrial respiratory chain (15)(16)(17). The side chains of select amino acids also can serve as waystations for redox hopping reactions, with Cys, Met, Trp, and Tyr being the most likely candidates (18).…”
mentioning
confidence: 99%